Equipment for cleaning and washing works - Parapanov, A. (Запоріжжя : ТДАТУ, 2024)
EN: Cleaning and washing equipment is divided into equipment for cleaning and sanitary treatment of the car body, equipment for washing cars, equipment for blowing and drying cars after washing, in addition, auxiliary equipment is used designed for regenerating used water under production conditions. Equipment for the mechanization of cleaning work and sanitary treatment of the car body. To remove dust and debris from the body of a bus and a passenger car, from the cab and from the platform of a truck, electric vacuum cleaners and dust suction units of stationary, mobile or portable (manual) type are used. To clean the interiors of passenger cars, buses, truck bodies and special vans, vacuum cleaners with electric motors with a power of 0.3...7 kW, respectively, are used. Car washing equipment is divided into general and special.
Keywords: sanitary treatment; cleaning; washing equipment